The Influence of Digital Transformation on the Competitiveness of MSMEs with Performance as a Mediating Variable : A Study on MSMEs in Kediri City - Dian Arini; Mochammad Reza Zulfikar; Hermono Widiarto (The Indonesian Institute of Science and Technology Research, 2026)
The contemporary business ecosystem environment continues to evolve rapidly, particularly with the advent of the Fourth Industrial Revolution. Businesses now have to adjust to a more competitive and digitally focused environment if they are to survive. This research is aimed at understanding the effects of digital transformation of MSMEs and its effects on competitiveness, as well as MSME performance, and the impact of digitization on the MSME performance of MSMEs in the City of Kediri. 390 respondents were sampled for the given study, and the data were analyzed using Structural Equation Modeling and Partial Least Squares Sem analysis. Findings support the theory that digital transformation impacts the MSME performance positively. Furthermore, it positively impacts the MSME's competitiveness. This is further demonstrated in the research, as the performance is stated to have a positive impact on their competitiveness. With the business performance improved financially, operationally, and in marketing, MSME's ability to generate value and strengthen a customer base and market position is enhanced. MSME performance mediates the influence of digital transformation on MSME competitiveness.